Desain Interior Sebagai Fasilitator Interaksi Sosial: Analisis Wisata Kuliner Di Ruang Kreatif Bandung. - Hadi, Nefi Salsabila; Nefi Salsabila; Joedawinata, Ahadiat (ARTic, 2025)
The transformation of public spaces in urban areas often reflects a response to changes in lifestyle and patterns of social interaction. One form of such transformation can be found in the revitalization of the second floor of Pasar Kosambi, Bandung, which is now known as The Hallway Space. This space offers a more contemporary interior design approach, targets the needs of the younger generation, and demonstrates an effort to make traditional spaces a new platform for more inclusive social and economic activities.  This research aims to examine the extent to which the space-forming elements, namely the floor, walls and ceiling, play a role in facilitating social interaction in a semi-commercial culinary space. The approach used is descript-+ive-qualitative, with field observation methods and an in-depth literature review o/f interior element theory and the concept of third space. The research focused on the culinary tenant area and communal dining room as the main center of user activities.  By considering interior design as an active element in shaping social experience, this study highlights the interrelationship between the structure of space and the dynamics of user interaction. This research is expected to enrich the understanding of how creative public spaces act as facilitators of social relations in the context of contemporary cities, as well as open new discussions on the role of design in supporting the formation of adaptive and relevant third spaces Keywords: Interior Design, Third Space, Space Elements, The Hallway Space, Social Interaction